Circulating myeloid cells invade the central nervous system to mediate cachexia during pancreatic cancer - Burfeind, Kevin G; Zhu, Xinxia; Norgard, Mason A; Levasseur, Peter R; Huisman, Christian; Buenafe, Abigail C; Olson, Brennan; Michaelis, Katherine A; Torres, Eileen RS; Jeng, Sophia; McWeeney, Shannon; Raber, Jacob; et al. (eLife, 2020)
Weight loss and anorexia are common symptoms in cancer patients that occur prior to initiation of cancer therapy. Inflammation in the brain is a driver of these symptoms, yet cellular sources of neuroinflammation during malignancy are unknown. In a mouse model of pancreatic ductal adenocarcinoma (PDAC), we observed early and robust myeloid cell infiltration into the brain. Infiltrating immune cells were predominately neutrophils, which accumulated at a unique central nervous system entry portal called the velum interpositum, where they expressed CCR2. Pharmacologic CCR2 blockade and genetic deletion of Ccr2 both resulted in significantly decreased brain-infiltrating myeloid cells as well as attenuated cachexia during PDAC. Lastly, intracerebroventricular blockade of the purinergic receptor P2RX7 during PDAC abolished immune cell recruitment to the brain and attenuated anorexia. Our data demonstrate a novel function for the CCR2/CCL2 axis in recruiting neutrophils to the brain, which drives anorexia and muscle catabolism.
Keywords: cachexia; neuroimmunology; neutrophils; brain; pancreatic cancer; myeloid cells